DAMPAK PENGGUNAAN APLIKASI TIKTOK DALAM PEMBELAJARAN IPA KELAS VI SDN KARANGGAN 03 - Sartika Komalasari; Fahmi Irfani; Khaidir Fadil (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
This study aims to determine the impact of using the TikTok application on students' learning processes in science learning class VI at SDN Karanggan. This study uses a qualitative research method with a case study approach. The results of the study show that the use of the TikTok application by children and adolescents has an impact on students' learning processes in learning science. There are 2 impacts, namely: positive impact and negative impact. The positive impacts that arise include: (1) increasing self-confidence in students to be more active during the learning process, (2) Can be used as a forum for developing creativity, (3) makes it easier for students to make new friends, entertainment, information, (4) Provide enthusiasm for learning. While the second impact of using the TikTok application on the student learning process is a negative impact, namely: (1) Reducing students' curiosity about the subject matter, (2) Reducing interest in learning and reading learning materials, (3) Students feel more easily tired and sleepy during the learning process, (4) decreased learning outcomes and achievement, (5) language changes. There are impacts that arise, requiring classroom teachers to try to minimize these impacts. Efforts made by the teacher are: making the TikTok application a science learning medium for grade VI students, and working with parents to provide directions and control the use of gadgets.